The Differing Strategies of Agricultural Cooperatives in Thailand: from Managing Market Links to Self-Reliance - Faysse, Nicolas; Onsamrarn, Wattanai (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018DO - 10.14456/jcdr-hs.2018.14, 2018)
Because of their dual nature as business enterprises and social groups, agricultural cooperatives have to adapt to socio-economic changes taking place in members’ farms and in their environment. The present study analyses the activities of 23 Thai agricultural cooperatives and examines how these activities delineate strategies to adapt to the socio-economic transformations in rural areas of Thailand. All cooperatives organized the supply of agricultural inputs and almost all of them were engaged in loans and savings. The choice of implementing other activities was related to two main strategies. One was to manage market links, thanks for instance to joint marketing of members’ products, in order in particular to deal with decreasing market prices. The other one was to promote members’ self-reliance, i.e., their capacity to obtain a living without fully depending on the marketing of their agricultural products. This strategy aimed in particular to adapt to farmers’ ageing and was achieved for instance thanks to diversification of agricultural products so as to increase home consumption of these products, or through bartering between cooperatives. Some cooperatives actively implemented one or two of these strategies (as they are not antagonistic) while others did not engage in any of them. Overall, cooperatives managed to adapt to the decreasing role of agriculture in rural areas. However, many of studied cooperative have to develop new ways of supporting their members if they want to remain key players when it comes to the successful integration of farmers in the agricultural economy. Keywords: Agricultural Cooperatives, Self-Reliance, Socio-Economic Changes, Thailand